SEMI-EMPIRICAL METHODS BASED 3D-QSAR STUDIES FOR SOME SUBSTITUTED SCHIFF BASES OF PYRIDINE-2-AMINE - KISHOR ARORA, (International Journal of Pharma and Bio Sciences, 2014)
3D QSAR viz. 3 descriptor quantitative structure and activity relationship studies for a series of compounds i.e. Schiff base derivatives of 4-methyl pyridine-2-amine involving their semi-empirical quantum chemical descriptors and their laboratory reported activities against pathogen viz. P.aeruginosa has been carried out and reported in the present paper. Graphs between observed and predicted activities, both in the terms of p(MIC) are also being reported on the basis of which this may be concluded that some parameters/descriptors have positive contribution towards the activity. The method has been proved to be a useful tool for such type of studies.